2012
DOI: 10.1159/000335713
|View full text |Cite
|
Sign up to set email alerts
|

How Much Remnant Is Enough in Liver Resection?

Abstract: Background: Liver resection represents the first choice of treatment for primary and secondary liver malignancies, offering the patient the best chance of long-term survival. The extensive use of major hepatectomy increases the risk of post-hepatectomy liver failure (PHLF), which is associated with a high frequency of postoperative complications, mortality and increased length of hospital stay. Aims: The aim of this review is to investigate the different risk factors related to the occurrence of PHLF and to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
213
0
17

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(233 citation statements)
references
References 204 publications
3
213
0
17
Order By: Relevance
“…The remnant liver must therefore be able to overcome the necrosis, preserving or recovering an adequate synthetic ability [22] ; as a consequence, there must be an adequate and functional FLRV to avoid PHLF [23] . Despite this, there is no uniform consensus among hepatic surgeons on the amount of liver volume that can be safely resected, with a wide range of reported values [24,25] . Guglielmi et al [24] reported that in patients with "healthy" liver (absence of hepatic diffuse disease, normal functionality tests) the limit of FLRV% for a safe resection varies between 20% and 30%, while in patients with underlying hepatic disease (cirrhosis, cholestasis, steatosis) the critical FLRV% value rise up to 30%-40%.…”
Section: Introductionmentioning
confidence: 99%
“…The remnant liver must therefore be able to overcome the necrosis, preserving or recovering an adequate synthetic ability [22] ; as a consequence, there must be an adequate and functional FLRV to avoid PHLF [23] . Despite this, there is no uniform consensus among hepatic surgeons on the amount of liver volume that can be safely resected, with a wide range of reported values [24,25] . Guglielmi et al [24] reported that in patients with "healthy" liver (absence of hepatic diffuse disease, normal functionality tests) the limit of FLRV% for a safe resection varies between 20% and 30%, while in patients with underlying hepatic disease (cirrhosis, cholestasis, steatosis) the critical FLRV% value rise up to 30%-40%.…”
Section: Introductionmentioning
confidence: 99%
“…The predicted LiMAx value after surgery is approximately 31% of 639 µ g/kg/h. This value of 198 µ g/kg/h is below the normal liver capacity, but in a range in which the recovery of the liver is expected without complications [21,30,[32][33][34][35][36]. Thus, it is possible to predict this operation is safe.…”
Section: Operation Planningmentioning
confidence: 93%
“…However, in order to replace the vital functions of a human liver and allow patient survival, a much larger mass (>25%) is needed 43. This ambitious goal is the core aim of the whole organ decellularization–recellularization technology that is covered in the next section.…”
Section: Implantable Technologies For Liver Therapiesmentioning
confidence: 99%